THE PRINCIPLES OF DEMOCRACY: A CONCEPTUAL FRAMEWORK FOR LEVERAGING DEMOCRATIC POLARITIES - Inesia - Forde, Angelina (AGPE THE ROYAL GONDWANA RESEARCH JOURNAL OF HISTORY, SCIENCE, ECONOMIC, POLITICAL AND SOCIAL SCIENCE, 2023)
The polarities of democracy is used to achieve human emancipation by simultaneously managing multiple paradoxes. Johnson’s polarity management is incorporated into the polarities of democracy as the conceptual framework. Although Johnson’s framework may be appropriate for managing other tension-dependent pairs, it is less suitable for managing multiple democratic values when the goal is human emancipation and sustainable democratic social change. Managing multiple polarities is exacerbated by the problem-shifting and problem-creation effect inherent in a tension-driven framework. The aim was to develop a constructivist grounded theory to answer the research question: How can the first principles of democracy be used to reduce dynamic tension and achieve human emancipation? This gap has been filled by a parsimonious conceptual framework based on three democratic principles: human dignity, fairness, and knowledge. The principles of democracy conceptual framework can synthesize the tension between democratic values in order to manage, plan, and evaluate democratic social change initiatives.